Antimicrobial activity of a quaternary ammonium methacryloxy silicate-containing acrylic resin: a randomised clinical trial - Liu, Si-ying; Tonggu, Lige; Niu, Li-na; Gong, Shi-qiang; Fan, Bing; Wang, Liguo; Zhao, Ji-hong; Huang, Cui; Pashley, David H.; Tay, Franklin R. (Scientific reports, 2016)
Quaternary ammonium methacryloxy silicate (QAMS)-containing acrylic resin demonstrated contact-killing antimicrobial ability in vitro after three months of water storage. The objective of the present double-blind randomised clinical trial was to determine the in vivo antimicrobial efficacy of QAMS-containing orthodontic acrylic by using custom-made removable retainers that were worn intraorally by 32 human subjects to create 48-hour multi-species plaque biofilms, using a split-mouth study design. Two control QAMS-free acrylic disks were inserted into the wells on one side of an orthodontic retainer, and two experimental QAMS-containing acrylic disks were inserted into the wells on the other side of the same retainer. After 48 hours, the disks were retrieved and examined for microbial vitality using confocal laser scanning microscopy. No harm to the oral mucosa or systemic health occurred. In the absence of carry-across effect and allocation bias (disks inserted in the left or right side of retainer), significant difference was identified between the percentage kill in the biovolume of QAMS-free control disks (3.73 ± 2.11%) and QAMS-containing experimental disks (33.94 ± 23.88%) retrieved from the subjects (P ≤ 0.001). The results validated that the QAMS-containing acrylic exhibits favourable antimicrobial activity against plaque biofilms in vivo . The QAMS-containing acrylic may also be used for fabricating removable acrylic dentures.